Islamic Cooperative Financial Reports based on Regulation of Minister of Cooperatives and SMEs Republic of Indonesia No.14/Per/M.UMKM/IX/2015: Case Study of ABC Academic Community Cooperative - Siti Solihatul Munfariha; Murniati Mukhlisin (Penerbit Goodwood, 2024)
Purpose: The aim of this study is to analyze the preparation of Kosika ABC's financial reports based on the Ministry of Cooperatives and SMEs, Republic of Indonesia No.14/Per/M. UMKM/IX/2015. Research Methodology: This paper adopts a case study method with standardization of the final reporting approach to evaluate how accounting is applied in preparing Kosika Academic Community Cooperative (ABC) financial reports at the end of the period. Results: The results of the research show that the financial report presented by Kosika ABC, such as the financial position and calculation of overall business results, is acceptable, but the Kosika ABC financial report that has been presented is still not in accordance with the components of the financial report according to the said regulation. Conclusions: The conclusion of this research is that the suitability of the Kosika ABC financial report to the regulation if, in presentation form, the overall Financial Report is 28.57 %. Limitations: This case study has several limitations, such as comparative work with other cooperative/s, analysis of several years of financial reports, evaluation of the details of each report, and interview sessions with cooperative operators outside Kosika ABC for triangulation purposes. Contributions: This case study contributes to the awareness among Islamic cooperative practitioners that they must refer to appropriate reporting guidelines for accountability purposes.